Pengambilan keputusan berbasis data untuk perencanaan pendidikan: strategi untuk keberhasilan kepala sekolah - M Nurzen S (Jurnal Konseling dan Pendidikan, 2022)
Data-based planning occupies a very important role in determining the success of schools or educational institutions in determining the right strategy to improve the quality of the education provided. Decision-making that is not in favor of student learning interests still often occurs in schools or educational institutions. This study aims to examine the forms and patterns of decision-making and formulate concrete efforts to design data-based plans in schools that are in favor of increasing student learning outcomes and achievements. This study took data from 20 schools spread across Jambi Province. Participants consisted of school principals, teachers, school committees, and students. The sample used was taken randomly. The process of collecting data through interviews, observation, and document review. The results of this study indicate that planning in schools is based on fulfilling administrative needs and accountability, the data collected has not been used as a basis for making decisions to improve student learning processes and outcomes. In general, several stages of decision-making are carried out, namely: identification of problems or issues faced, data collection, evaluation of alternatives, selection of alternatives, and implementation of decisions. The challenges of cultivating data-based planning at the school level are data availability, human resource competence, support from related parties, and organizational culture.